2016
DOI: 10.1097/nmd.0000000000000465
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Anxiety Sensitivity on a Wish to Die in Complicated Grief

Abstract: Individuals with complicated grief (CG) are at elevated risk for suicidal thoughts. Anxiety sensitivity has recently emerged as a risk factor of suicide. This study aimed to investigate a possible association between anxiety sensitivity and a wish to die in individuals with CG. Participants were evaluated for participation in a treatment study and completed an ancillary questionnaire-based study. Participants were 51 bereaved adults evaluated (age: M = 54, SD = 13.6; 78% (n=40) women). Logistic regression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…A larger sample with more detail about the timing of CG and depression onset as well as suicide attempts may be needed to determine if CG has a unique contribution to increased suicide attempt risk in this population. Prior data have supported increased rates of suicidal ideation and behavior in individuals with CG, and these rates may be even greater among suicide survivors, indicating the need to continue investigations of the relationship between suicide and CG across other populations (Baker et al, ; Mitchell, Kim, Prigerson, & Mortimer‐Stephens, ; Young et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A larger sample with more detail about the timing of CG and depression onset as well as suicide attempts may be needed to determine if CG has a unique contribution to increased suicide attempt risk in this population. Prior data have supported increased rates of suicidal ideation and behavior in individuals with CG, and these rates may be even greater among suicide survivors, indicating the need to continue investigations of the relationship between suicide and CG across other populations (Baker et al, ; Mitchell, Kim, Prigerson, & Mortimer‐Stephens, ; Young et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, greater social anxiety predicted greater thwarted belongingness in place of social AS, suggesting that broader anxiety about social interactions may better account for the relationship between social AS and thwarted belongingness. Other studies have yielded mixed results regarding the relationship between social AS and suicide risk: one found that greater AS social concerns were associated with a “wish to die” in individuals with complicated grief (Baker et al., ), whereas another study found no association between social AS and SI (Capron, Lamis, et al., ). A third study found an association between greater social AS and a history of past suicide attempts, but not SI (Capron, Fitch, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a primary diagnosis of GAD and participants without any psychiatric diagnosis (healthy controls, HC) were enrolled in a larger ancillary study at the Center for Anxiety and Traumatic Stress Disorders at the Massachusetts General Hospital between 2003 and 2017 [46][47][48]. Eligible participants were willing and able to sign informed consent and over the age of 18.…”
Section: Participantsmentioning
confidence: 99%